Presence of high-risk human papillomavirus sequences in breast cancer tissues and association with histopathological characteristics - Kroupis, C.; Markou,A.; Vourlidis,N.; Dionyssiou-Asteriou, A; Lianidou,E.S. (Clin.Biochem., 2006)
OBJECTIVE: To examine the presence of human papillomavirus (HPV) in breast cancer tissues. DESIGN AND METHODS: Four different PCR methods for detection and verification of genital HPVs were applied in frozen breast cancer specimens. Tumors were also evaluated for various histopathological parameters. RESULTS: Seventeen samples out of 107 tested positive (15.9%). HPV RFLP typing identified a total of 21 high-risk viruses: fourteen HPV 16 (67% of all detected HPV types), three HPV 59, two HPV 58, one HPV 73 and one HPV 82 (one sample with double infection and two samples with triple infection). Breast cancer patients harboring high-risk HPV DNA sequences in their tumor were younger than the rest of the patients. Furthermore, they were less estrogen-receptor-positive and more proliferative as observed in the corresponding indices: Ki-67 staining, S-phase/proliferative fractions and percentage of cells with DNA content over 5C. CONCLUSION: The presence of high-risk HPV DNA sequences in the breast cancer tissues studied was verified, and a possible association with acceleration of malignancy was examined
DA - 20060717 IS - 0009-9120 (Print) IS - 0009-9120 (Linking) LA - eng PT - Journal Article RN - 0 (DNA, Viral) RN - 0 (Ki-67 Antigen) RN - 0 (Tumor Suppressor Protein p53) RN - EC 2.7.10.1 (Receptor, ErbB-2) SB - IM
Keywords: Adult; analysis; Breast Neoplasms; Dna,Viral; Female; genetics; Greece; Humans; Ki-67 Antigen; metabolism; methods; Middle Aged; Papillomaviridae; Papillomavirus Infections; pathogenicity; pathology; polymerase chain reaction; Polymorphism,Restriction Fragment Length; Receptor,ErbB-2; Tumor Suppressor Protein p53; virology